Managerialism in Civil Service: A Comparison of France and Finland - Salovaara, Tuulia (My University, 2008)
There are surprisingly many similarities between France and Finland. The membership of the European Union is perhaps the most well known similarity. The top executive systems have been very distant from each other previously but now they may become more similar if the proposed top executive system will be implemented in Finland. Managerialism is studied in a theoretical sense because its characteristics are highly attached to the civil service system of today. Managerialism can be seen as a management style of the business world which has found its way to the public sector. The notion of managerialism in the civil service system is researched. The top executive system in France and Finland is both studied and compared. The extent of convergence and divergence between France and Finland are researched from many points of view. The method is a combination of both qualitative and comparative methods. The case-oriented comparative methods are close to the comparative method used here. The inferences are based on actual information which was directly obtained from the organisations such as the OECD, the EU and locally produced sources from the both countries. It has been shown that the idea of historical aspects is a connecting characteristic for both civil service systems. The French civil service system is more attached from the history than the Finnish system. More reforms have been made in the Finnish public administration than in France. International influence has been more important in Finland than it may be thought. Managerialism represents an opportunity for leadership on an individual basis. It may seem that managerialism only touches the top executive class but it has an influence on social groups, socially organised and influenced groupings. The public administration has always been in contact with politics thus the consequences of unthought-of decisions have be considered even more than before. The civil service system can be seen as subordinate to politics. At same time, the civil services of both France and Finland can be seen as a political force. Today, a top executive civil servant has to be a multitalented person understanding the political processes amongst other things. The proposed top executive system would fulfil the guarantee of ipso facto, which is a reality in the French top executive system. This can be seen as an influence of the Continental tradition of administration.
Keywords: managerialism; civil service system; top executive system; France; Finland; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|